Tax convergence within economic integration frameworks: Post-COVID trajectories - Elena F. Kireeva; Alan K. Karaev (Journal of New Economy)
During the times of crisis, the role of fiscal policy when ensuring macroeconomic stability and fostering economic growth within integration associations increases. Tax policy is a pivotal parameter in the formation of state budgets and significantly impacts population income, while the convergence of tax systems has gained prominence as a means of bringing integrating states closer together. Therefore, it is imperative to evaluate the convergence processes of tax systems within integration associations. In the study, we explore the convergence hypothesis in relation to the tax systems of a group of post-Soviet countries: Armenia, Belarus, Kazakhstan, Kyrgyzstan, and Russia. Methodologically, the research relies on the convergence theory in economics, process and systems approaches. The method is based on the concept of sigma-convergence, and calculation of Frank indices. The dataset utilized for analysis spans a decade, from 2012 to 2022, and comes from the Eurasian Development Bank (EDB). The findings reveal that the sigma-convergence of tax policy within the group of countries belonging to the Eurasian Economic Union (EAEU) was present before the onset of the coronavirus pandemic. However, with the pandemic’s spread, an uncoordinated tax policy to support the national economies emerged, which has led to the tax systems’ divergence. The study underscores the necessity of establishing automatic crisis management mechanisms for fiscal interventions at the supranational level within the EAEU. Such mechanisms would enable a coordinated response to future humanitarian and financial shocks, enhancing the resilience of EAEU member states.